Foreign Direct Investment and child health outcomes in Africa - Mustapha Immurana; Abdul-Aziz Iddrisu; Samuel Owusu; Hadrat Mohammed Yusif (Cogent Economics & Finance, 2023)
While several studies have examined the effect of Foreign Direct Investment (FDI) on economic development indicators, most of these studies focused on economic growth with very little attention paid to health outcomes. Moreover, among the studies that took account of health outcomes, none of them investigated the effect of FDI on child health outcomes across a sample of African countries. However, focusing on African countries is very important because sub-Saharan Africa (SSA) has the highest rate of child mortality in the world. This study, therefore, investigates the effect of FDI on child health outcomes in 39 African countries from 1980 to 2018. Neonatal and infant mortality rates are used to proxy child health outcomes. The baseline estimation technique employed is the Fixed Effects (FE) regression. However, to deal with potential endogeneity, we employ the system Generalised Method of Moments (GMM) regression as the robustness estimation technique. Our findings show that, FDI improves child health outcomes, especially through economic growth after controlling for endogeneity. Thus, in African governments' quest to reduce child mortality, a major useful strategy could be attracting more FDI inflows.
Keywords: C33; C36; F2; I1; O55; 330; Africa; child health; Foreign Direct Investment; infant mortality; neonatal mortality